Effects of Dietary Supplementation of Bovine Lactoferricin on Rumen Microbiota, Lactation, and Health in Dairy Goats - Shao, Yuexin; Zhang, Xian; Zhang, Huawen; Tian, Bowen; Weng, Yunan; Huang, Jiangtao; Lu, Christopher D.; Shi, Huaiping (Frontiers in Nutrition, 2021)
This study aimed to investigate the biological effects of supplementation of bovine lactoferricin (BLFc) at the rate of 100 mg/kg/day (LF-1) or 200 mg/kg/day (LF-2) in lactating dairy goats. Dietary BLFc supplementation increased the concentration of lactoferrin (LF) in the milk and serum (p < 0.05) without affecting the feed intake. In the LF-1 group, serum Fe, total antioxidant (T-AOC), and immunoglobulin A (IgA) were increased (p < 0.05), while malondialdehyde (MDA) was decreased (p < 0.05). In the LF-2 group, ruminal fluid pH value was decreased (p < 0.05), and the composition of ruminal microflora on day 42 was more diversified. Firmicutes phylum in the LF-2 group was the most abundant phyla. In contrast, Bacteroidetes phylum in the control group and the LF-1 group were the most abundant. Lower milk somatic cell count and higher IgA were observed in the LF-1 group and the LF-2 group than those in the control group (p < 0.05). These results suggested beneficial effects of supplementation of 100 mg/kg/day BLFc on reducing the oxidative stress and altering diversity of ruminal microflora.